Hubungan Tingkat Pengetahuan, Sikap, dan Kecemasan Ibu Hamil terhadap Kunjungan Antenatal Care pada Masa Pandemi COVID-19 di Puskesmas Glugur Darat, Kecamatan Medan Timur - Siahaan, Gerald Osson Fransiska; Simanjuntak, Leo; Simanjuntak, Novita Hasiani (Universitas HKBP Nommensen, 2023)
Background: During the COVID-19 pandemic in Indonesia, 1086 pregnant women and 302 babies died from COVID-19 infection in 2021. The high mortality rate affecting ANC visits was seen from the decrease in ANC coverage, influenced by knowledge, attitudes, and anxiety. Purpose: To determine the relationship between knowledge, attitudes, and anxiety towards ANC visits during the COVID-19 pandemic at Glugur Darat Health Center, East Medan Anxiety. Methods: The analytic observation with cross-sectional study was conducted at Glugur Darat Health Center, Medan Timur District using a total sampling technique that fulfill the inclusion criteria. The sample was third-trimester pregnant women who were recorded as having ANC. Data analysis used Chi-square with alternative fisher's exact test and backward multiple logistic regression Results: From the 66 respondents, it was found that pregnant women who performed ANC well were 46 respondents (69.7%), with high knowledge were 59 respondents (89.4%), with a positive attitude 65 respondents (98.5%), and had anxiety as many as 55 respondents (83.3%). Result data showed that knowledge related to ANC visits (p= 0,023) with OR = 5.6, anxiety related to ANC visits (p= 0,014) with OR = 4,6 and attitude not related to ANC visits (p= 0,303) Conclusion: There is a relationship between pregnant women's knowledge and anxiety about ANC visits and no relationship between pregnant women's attitudes towards ANC visits during the COVID-19 pandemic at Glugur Darat Health Center and the most influencing variable is anxiety.